Taiwanese Smallholder Farmers’ Perceptions and Barriers to Adopting Facebook - Chia-Wei Chang; James R. Lindner (Journal of International Agricultural and Extension Education, 2017)
Social media is an effective tool used in extension services and mass/distance education. Facebook is a successful social network site for information gathering and sharing. Facebook's penetration rate is higher in Taiwan than in any other Asian country. The purpose of this study was to determine the influences of selected factors on the adoption of Facebook by Taiwanese smallholder farmers. The study examined smallholder farmers’ perceptions of Facebook according to Rogers’ (2003) characteristics of an innovation and smallholder farmers’ perceptions of potential barriers to adopting Facebook. Three hundred and fifty one smallholder farmers participated in the survey research. Respondents were asked to rate their perceptions of Facebook and potential barriers to adopting Facebook: relative advantages, compatibility, complexity, trialability, observability, financial concerns, concerns about time, concerns about incentives, planning issues, and technology concerns. Respondents held positive perceptions of compatibility, complexity, observability, relative advantage, and trialability as characteristics of Facebook. Respondents neither agree nor disagree with respect to technology concerns, financial concerns, concerns about time, planning issues, and concern about incentives for the adoption of Facebook. Future research should focus on perceptions of potential barriers by smallholder farmers who were in early and middle stages of the innovation-decision process. This may help extension services understand better the barriers that slow down the speed of Facebook adoption by smallholder farmers.
Keywords: Adoption; Diffusion; Taiwan; Smallholder farmers; Facebook